Konservasi sebagai landasan perencanaan lansekap berbasis tempat pada masyarakat Baduy Dalam di Kabupaten Lebak Provinsi Banten - Chairuman, Mohamad (Fakultas Kehutanan Universitas Mulawarman, 2024)
The Baduy clan is one of the native Sundanese clans that actually sticks to its traditions precursors, their lives are committed to satisfying the order of their predecessors in securing equilibrium and congruity of the universe. Advancement exercises, neighborhood environmental change andGlobalization represents a danger to conventional clans, like the Baduy clan too. The consequences of the grouping and bioregional examination of the Baduy Dalam scene can be arranged into 103 place unit. Assessment is done at every area unit in light of dangers and issues every unit. The principal issue found in the Inward Baduy scene is its restricted size accessibility of agrarian land assets which can be utilized in turn so that has suggestions for diminishing area richness. Then again, the populace development rate is very high requests an expansion in the requirement for farming creation land. The answer for this issue was understood as a scene plan created in light of the idea of partitioning space with adjusting land use for useful purposes to have the option to earn barely enough to get by. inhabitants for rural creation land. Scene plan executed in spatial plans (drafting), dissemination plans, and vegetation plans.